2023
DOI: 10.1177/03000605231187939
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parsonage–Turner syndrome with COVID-19 infection and vaccination: a systematic review

Muhammad Zain Ameer,
Ata Ul Haiy,
Muhammad Hassan Bajwa
et al.

Abstract: Objectives The exact etiology of Parsonage–Turner syndrome is unknown, but it is known to be preceded by infection, vaccination, or surgical intervention. In this review, we describe associations of Parsonage–Turner syndrome with COVID-19 infection and vaccination. Methods A systematic literature search was conducted using PubMed/MEDLINE, ScienceDirect, and Google Scholar. Microsoft Excel was used for data extraction and statistical analysis. The quality of case reports and case series was assessed using the J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Interestingly, there has recently been a significant number of reported cases of brachial neuritis following both COVID-19 vaccination and COVID-19 infection, further suggesting an autoimmune precedent [7][8][9][10][11][12][13]. One systematic review analyzed 68 patients, 32 post-vaccination and 34 post-infection with COVID-19, who experienced brachial neuritis following vaccination or infection [7]. Another recent report noted 42 specific cases reported following vaccination [12].…”
Section: Discussion Etiologymentioning
confidence: 99%
“…Interestingly, there has recently been a significant number of reported cases of brachial neuritis following both COVID-19 vaccination and COVID-19 infection, further suggesting an autoimmune precedent [7][8][9][10][11][12][13]. One systematic review analyzed 68 patients, 32 post-vaccination and 34 post-infection with COVID-19, who experienced brachial neuritis following vaccination or infection [7]. Another recent report noted 42 specific cases reported following vaccination [12].…”
Section: Discussion Etiologymentioning
confidence: 99%
“…The case study concerned a female who was old, while in the country, the total number of cases was only 82 [ 40 ]. COVID-19 has been linked to a less-known Parsonage–Turner syndrome, usually manifested by sudden severe shoulder pain followed by motor weakness [ 41 ] or with an appearance later neuromuscular disorders [ 42 ]. In addition, myasthenia gravis can be included in the neuromuscular junction disorders that occurred in three patients without previous neurological or autoimmune disorders [ 43 ].…”
Section: Neurological Symptoms Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…A recent systematic review analyzed 26 reported cases of PTS following the administration of the SARS-CoV-2 vaccine [ 2 ]. Another systematic review suggested an association not only with COVID-19 infection but also after vaccination, with an earlier onset of PTS symptoms post-vaccination compared to the infection itself [ 4 ]. It typically affects adult males more frequently with a sudden onset [ 5 ], and sometimes atypical manifestations can occur, such as lower limb and diaphragmatic deficits [ 6 ].…”
Section: Introductionmentioning
confidence: 99%